(untitled) (Third Sector Social Economic Review, 2021)
First of all, it is predicted that the negative effects of the attempts to contain the Covid-19 virus(stay at home and travel restrictions, etc.), which emerged in China and spread to the world in a short time, on the economy will emerge more prominently as the end of the year approaches. The airway industry, which is a demand-oriented sector, has an important role in the rapid spread of the virus. Serious restrictions have been imposed on the industry for this. Due to these restrictions; The airway industry is one of the sectors most affected by the Covid-19 process. In this context; by using the interim financial reports of the enterprises for the years 2019-2020, who are in air transportation operations in Turkey and located in BIST 100 index, financial performances and industry-specific indicators have been compared. In addition, by examining the financial statement footnotes with the ""content analysis method"", the level of informing enterprises provide about Covid-19 was determined. According to the results of the study, it is seen that Covid-19 led to a negative impact on Turkish air transport. It has been determined that this effect is mostly felt in the second and third quarters, and financial reports include explanations for Covid-19, but differ between enterprises.